A discussion of problems in implementing organisational cultural change: Developing a learning organisation in University Libraries. Issue 6 (7th September 2015) - Limwichitr, Saowapha; Broady-Preston, Judith; Ellis, David
Abstract : Purpose: – The purpose of this paper is to review the literature on organisational cultural change and problems in its implementation, focussing on the case of building a learning organisation (LO) within university library context. Design/methodology/approach: – Key literature published within Library and Information Science, Business and Management and other related fields were reviewed to identify themes regarding organisational cultural change in relation to development of an LO emerging in the recent years. Findings: – Reviewed literature in this paper highlights key challenges in examining organisational cultural change for the purpose of building an LO. These include a lack of an agreed definition of the LO concept, practical approaches and measure for assessing achievement of the cultural change. A need for in-depth studies which focus on current practices and related problems in this regard is also revealed, and the systems approach is proposed as a suitable approach for holistic investigation of all critical elements that possibly affect establishment of an LO. Originality/value: – The paper raises awareness of the importance of examining organisational cultural change as a critical supportive influence of developing an LO. Problems to be considered in its implementation are synthesised and served as a basis for further investigation in the author's doctoral research project.